Low‐pressure fabrication of IR‐transparent Y2O3 via spark plasma sintering. (1st November 2016) - Irom, Elnaz; Zakeri, Mohammad; Ahangari Hossein Zadeh, Ali Sedaghat; Safian, Saman; Rahbari, Ali
Abstract : Different pressures of 80 and 90 MPa were applied to produce Y2 O3 ceramics by spark plasma sintering in this work. Effects of pressure were investigated on densification, microstructure, infrared (IR) transmission and mechanical properties. It was found that applying higher pressure led to finer microstructure and consequently higher hardness and fracture toughness. An IR‐transparent Y2 O3 ceramic with 60% transmission at wavelength of 5 µm was obtained by sintering at 1300°C under uniaxial pressure of 90 MPa. This sample had an average grain size of 0.76 µm and hardness and fracture toughness of 9.37 GPa and 1.60 MPa.m 1/2, respectively.